Feeding habits of redfish (Sebastes spp.) and Greenland halibut (Reinhardtius hippoglossoides) in West Greenland waters - Pedersen, S. A.; Riget, F. (ICES Journal of Marine Science, 1993)
A total of 2708 redfish and 3030 Greenland halibut stomachs were collect on the shrimp fishing grounds off West Greenland in summer and autumn 1990–1991 and in winter and spring 1992. The stomach contents of small redfish (5–19 cm) and small Greenland halibut (< 14 cm) were dominated by planktonic crustaceans. Hyperiids ( Parathemisto sp.) were the dominant prey in summer and autumn, copepods in winter, and euphausiids in spring. For larger redfish (> 20 cm) and larger Greenland halibut (> 14 cm), northern shrimp ( Pandalus borealis ) and juvenile redfish were important prey. Predator size and sampling period were found to influence the average degree of stomach fullness for redfish, but not for Greenland halibut. No influence of prey size preference of Greenland halibut for shrimp and redfish was found. Redfish was found to be the most important prey and shrimp the second most important prey in the diet of Greenland halibut. This study indicates that redfish is an important predator of shrimp, whereas Greenland halibut is an important predator of both redfish and shrimp.